Non-Thermal O2 Plasma Efficacy on C. albicans and Its Effect on Denture Base Resin Color - Christina Maillet; Serge Odof; Mikaël Meuret; Florian Le Bras; Frédéric Velard; Marie-Paule Gelle (Applied Sciences, 2021)
Denture stomatitis is a disease involving C. albicans, which can affect elderly and immuno-compromised people. To avoid any recurrence of this pathology, it is necessary to treat patients regularly and disinfect dentures. However, the denture cleansers’ efficacy is not optimal and often leads to adverse color effects on the denture base resins. The aim of this study was to investigate the efficacy of a low-pressure non-thermal O2 plasma (NTP) treatment on C. albicans seeded on ProBase®Hot resin (Ivoclar Vivadent). The viability reduction of C. albicans was assessed by colony forming units (CFU) analysis and by scanning electron microscopy (SEM). The effect of repeated treatments on the resin color was evaluated by spectrophotometry. The resin samples were placed in a sealed bag in which O2 plasma was generated in low-pressure conditions. The results showed that a 120-min O2 NTP treatment led to a 6-log reduction of C. albicans viability (p < 0.05) and to yeasts’ major alterations observed by SEM. Furthermore, significant slight color changes of the resin (∆E00 = 1.33) were noted only after six plasma treatments (p < 0.05). However, the denture aesthetic was preserved, as the color changes were not perceptible and remained below the acceptability threshold (∆E00 < 4).